Analisis Pengaruh Penanaman Modal Dalam Negeri, Penanaman Modal Asing, Tenaga Kerja Dan Ekspor Terhadap Pertumbuhan Ekonomi Sumatera Utara Tahun 2010 -2020 - Berliana Manurung, Zenifer Feby (Jurnal Manajemen Akuntansi (JUMSI), 2023)
North Sumatra's economic growth is an increase in economic value generated by all economic sectors in the North Sumatra region in a certain period of time, such as in one year or several years. This study aims to analyze the effect of domestic investment, foreign investment, labor, and exports on the economic growth of the city of North Sumatra in the 2010-2022 period. The data used in this research is secondary data from 2015 – 2020. The analytical tool used is multiple regression analysis. The software used to carry out the analysis was eviews 12. The results showed that domestic investment, foreign investment, and exports had a significant positive effect on the economic growth of the city of North Sumatra, while the workforce had no significant effect. In addition, the effect of domestic investment on economic growth is greater than that of foreign investment and exports. These findings can become the basis for local governments and business actors in developing economic policies in the city of North Sumatra.